Penerapan Range of Motion Pasif terhadap Gangguan Mobilitas Fisik pada Pasien Miastenia Gravis di RSUD Dr. Moewardi - Putri Widya Ariyani; Sri Puguh Kristiyawati (STIKes Ibnu Sina Ajibarang, 2025)
Myasthenia Gravis (MG) is a rare chronic disease caused by a neuromuscular disorder resulting from an autoimmune condition. The primary cause of MG is a thymus gland abnormality that produces an excessive amount of abnormal antibodies. These autoantibodies block signal transmission at the postsynaptic membrane of the neuromuscular junction. As a result, the signal transmission required for muscle contraction through acetylcholine receptor binding on muscle fibers becomes impaired. In Indonesia, MG prevalence remains low. The typical clinical manifestations include muscle weakness, such as ptosis, diplopia, limb weakness, dysphagia, speech difficulties, and respiratory failure. One progressive muscle weakness. Non-pharmacological management, which includes passive Range of Motion (ROM) exercises, involves joint movements that promote muscle contraction and enhance mobility. ROM serves as a rehabilitation intervention that improves muscle strength, increases joint flexibility, and prevents joint stiffness. During a six-day consecutive intervention, passive ROM exercises improved both muscle strength and limb range of motion. Prior to ROM administration, muscle strength and range of motion scores were recorded at and , respectively. After the intervention, muscle strength and range of motion scores increased to and These results indicate that passive ROM therapy can serve as a rehabilitation strategy to reduce physical limitations and improve the quality of life in patients with myasthenia gravis.